Palladium‐Catalyzed Highly Chemoselective Cascade Coupling‐Cyclization of Allenol Derivatives and Aryl Halides for the Construction of Dihydrobenzofuranols or Chromanols and Indolinols. Issue 10 (3rd September 2015) - Miao, Pingping; Wang, Hongkai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract A highly chemoselective, palladium‐catalyzed, cascade coupling‐cyclization of allenol derivatives containing multiple functional groups was developed. Through this reaction, a series of functional dihydrobenzofuranols or chromanols and indolinols was easily obtained in good to high yields.